2019
DOI: 10.1177/0892705719847244
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of CF-reinforced PLA parts manufactured by fused deposition modeling

Abstract: Many parameters of fused deposition modeling (FDM) influence the resulting mechanical properties. This can become a key factor if those parts are intended for commercial applications. This study focuses on the influence of nozzle temperature and infill line orientations for parts made with short carbon fiber (CF)-reinforced polylactic acid (PLA). Tests bars made of PLA and PLA-CF composite were produced under carefully selected conditions. As expected, PLA-CF yields higher tensile properties compared to PLA, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 29 publications
6
76
1
Order By: Relevance
“…A similar experiment was conducted by Magri et al [ 155 ] to investigate the effect of infill and the printing temperature of CF/PLA composite. With that, the optimum nozzle temperature and the print orientation to achieve higher tensile strength was obtained as 230 °C and [0°, 15°, −15°].…”
Section: Fibre-reinforced Composite Printingmentioning
confidence: 95%
“…A similar experiment was conducted by Magri et al [ 155 ] to investigate the effect of infill and the printing temperature of CF/PLA composite. With that, the optimum nozzle temperature and the print orientation to achieve higher tensile strength was obtained as 230 °C and [0°, 15°, −15°].…”
Section: Fibre-reinforced Composite Printingmentioning
confidence: 95%
“…Uniform distribution of additives ensures that agglomerates do not clog the printing apparatus or cause weak points in the printed material [ 11 ]. Compounding the complex nature of FDM 3D printing, various printing parameters—raster angle, raster width, layer thickness, build orientation, infill density and pattern, feed rate, and air gap—also have large effects on the quality and mechanical properties of FDM-printed parts [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of annealing heat treatment on polymer‐based parts, such as annealing, offers a multitude of advantages, like reduction of residual stresses, improvement of dimensional stability, reduction of defects, and improvement of physical and mechanical properties. [ 39 ] Recently, El Magri et al [ 22 ] studied the influence of annealing treatment on the crystallinity and mechanical properties of 3D printed PLA and short carbon fiber‐reinforced PLA. They found that annealing treatment at a low heating/cooling rate (2°C/min) improve significantly the degree of crystallinity, with favorable results on the mechanical properties of manufactured parts.…”
Section: Introductionmentioning
confidence: 99%